Perbandingan Pemodelan Struktur Menggunakan Metode Elemen Hingga: Studi Literatur Dari Berbagai Aplikasi Struktur Sipil Dan Mekanik - Arsenta, Kevin (Journal of Infrastructure and Construction Technology, 2024)
The Finite Element Method (FEM) is one of the most significant numerical approaches in structural analysis within civil engineering. FEM is widely used to analyze the behavior of complex structures by discretizing them into smaller elements. This article presents a literature review of nine studies that applied FEM to various structural objects: dams, various reinforced concrete (RC) structures, including infrastructure elements, high-rise buildings, and steel-based components. The review findings indicate that FEM is capable of providing accurate predictions of stresses, deflections, and failure patterns. However, its accuracy strongly depends on geometric modeling, material assumptions, boundary conditions, and validation against field data steel structures, and machine components. This article provides an in-depth understanding of the advantages, limitations, and future prospects of FEM in civil engineering applications.